Fuzzy Lyapunov exponent based onset detection of the epileptic seizures - Arunkumar, N.; Ramkumar, K.; Hema, S.; Nithya, A.; Prakash, Poornima; Kirthika, V. (2013 IEEE Conference on Information and Communication Technologies, 2013)
Various algorithms have been proposed for the detection of onset of epilepsy. Here we have used the Rosenstein algorithm to calculate the Largest Lyapunov exponent of the given Electroencephalogram (EEG) signal. We have combined this algorithm with fuzzy-rule based system. A fuzzy interference system is employed to detect the normal and the onset of epilepsy.